Early Detection of Children with Special Needs by Educators - Stephani Raihana Hamdan; Sulisworo Kusdiyati; Andhita Nurul Khasanah; Temi Damayanti Djamhoer (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2021)
The early detection of children with special needs is very important for educators, as they require special handling in the learning process so that they can develop optimally. The first important level for early detection is the early childhood education level. Early childhood teachers become agents who play a major role of early detection. Problems that occur due to late diagnosis of children with special needs often lead to learning and behavioural problems. If not handled properly, these disturbances will continue to the next level of further education. Knowledge of various types of disorders and early intervention in children with special needs must be the responsibility of early childhood education teachers to reduce the negative effects of any disruption that may occur. In order to assist teachers in early detection, this paper presents a study related to various developmental disorders that occur in children with special needs and the skills, techniques and steps that are needed for early detection.